Two Arabidopsis Mutants That Overproduce Ethylene Are Affected in the Posttranscriptional Regulation of 1-Aminocyclopropane-1-Carboxylic Acid Synthase - Woeste, Keith E. (American Society of Plant Physiologists, 1999)
The Arabidopsis mutants eto1 (ethylene overproducer) and eto3 produce elevated levels of ethylene as etiolated seedlings. Ethylene production in these seedlings peaks at 60 to 96 h, and then declines back to almost wild-type levels. Ethylene overproduction in eto1 and eto3 is limited mainly to etiolated seedlings; light-grown seedlings and various adult tissues produce close to wild-type amounts of ethylene. Several compounds that induce ethylene biosynthesis in wild-type, etiolated seedlings through distinct 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) isoforms were found to act synergistically with eto1 and eto3, as did the ethylene-insensitive mutation etr1 (ethylene resistant), which blocks feedback inhibition of biosynthesis. ACS activity, the rate-limiting step of ethylene biosynthesis, was highly elevated in both eto1 and eto3 mutant seedlings, even though RNA gel-blot analysis demonstrated that the steady-state level of ACS mRNA was not increased, including that of a novel Arabidopsis ACS gene that was identified. Measurements of the conversion of ACC to ethylene by intact seedlings indicated that the mutations did not affect conjugation of ACC or the activity of ACC oxidase, the final step of ethylene biosynthesis. Taken together, these data suggest that the eto1 and eto3 mutations elevate ethylene biosynthesis by affecting the posttranscriptional regulation of ACS.